In Vitro Inhibitory Effect of Cyperus rotundus L Crude Extracts on Mouth Isolates of Streptococcus mutans and Candida albicans - Najah A. M. (College of Pharmacy / Mustansiriyah University, 2012)
Streptococcus mutans is a normal flora bacteria found in human oral cavity, which cause dental caries and bad breathe oder. This project considered as an explorer study for the inhibitory effect of Cyperus rotundus L. crude extract on S. mutans and Candida albicans by agar well diffusion method. Extract of plant with three concentrations (8,16and 32 fold dilution of the MIC) were prepared and investigated for antibacterial activity. The minimal inhibitory concentration (MIC) against S. mutans of crude extract was 5 mg/ml. Crude extract also tested for antimicrobial susceptibility compared with standard antibiotic kanamycin. The three concentrations of the extract showed high effect on the growth of Streptococcus mutans. The means of inhibition zone diameters were 20.1, 23.4, and 25.2 mm for Streptococcus mutans. The largest inhibition zone 25.2 mm in diameter was observed in crude concentration 32 X MIC comparing to 17.3 mm in kanamycin. There was moderate effect of the three concentration of extract on the growth of Candida albicans, the means of inhibition zone diameters were 15.3, 20.1, and 21.0mm. The largest inhibition zone 21.0 mm in diameter was observed in crude 32 x MIC comparing to 16.7 mm in amphotreicin B. Although those results support the traditional use of Cyperus rotundus L. for the treatment of dental caries, further study is required for this medicinal plant.